PENERAPAN MODEL PROBING PROMPTING PADA MATERI MOMENTUM DAN IMPULS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMA PGRI PEKANBARU - Rabbani, Ashofiantika; Islami, Nur; Sudrajat, Hendar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study was aimed to determine students learning outcomes by the application of Probing Prompting model. This study was conducted in SMA PGRI Pekanbaru. This study was a quasi-experimental using intact group comparison design. The subject in this study was student of X MIPA class in SMA PGRI Pekanbaru. Subject on this study obtained from two classes based on homogeneity test and the sample was chooseen randomly so that experiment and control classed could be obtained. The data was collected by using students learning outcomes after Probing Prompting model was applied in experiment class and conventional learning was applied in control class. The data was analize by using descriptive analysis. This study showed that the average number of students absorption ability which Probing Prompting model was applied 79,46% and 71,00% for the conventional learning. It can be concluded that the application of Probing Prompting model could improve students learning outcomes in momentum and impulse at X class SMA PGRI Pekanbaru.Keywords : Probing Prompting model, students learning outcomes, descriptive analysis